Recurrent ST-elevation myocardial infarction: a case report of a rare complication of caseous mitral annular calcification. Issue 1 (11th December 2021) - Singh, Nikhil; Shah, Atman P; Torregrossa, Gianluca; Blair, John E
Abstract: Background: Caseous mitral annular calcification (MAC) is an under-diagnosed division of calcific mitral valve disease that has recently been reported to have increased propensity for embolic disease. Early recognition of this entity as a cause of embolic disease can lead to prevention of occlusive vascular disease and long-standing complications. Case summary: We present the case of a patient with end-stage renal disease who presented for evaluation of chest pain and was found to have ST-segment myocardial infarction. Despite thrombectomy and stenting, he had multiple recurrent events, and imaging evaluation demonstrated caseous MAC with mobile components. He was taken for surgical replacement of the mitral valve, with pathology confirming diagnosis. Discussion: Caseous MAC may represent an increased risk of embolic disease. Better understanding of this pathology and it's propensity for embolic disease will be important to best determine treatment plans and timing of operative intervention.